HUBUNGAN MENONTON CHANNEL YOUTUBE REMOTIVI TERHADAP PEMAHAMAN LITERASI MEDIA PADA KADER PELAJAR ISLAM INDONESIA YOGYAKARTA BESAR - Hersha Rahmawati; Abdul Rozak (Cakrawala Jurnal Penelitian Sosial, 2020)
Youtube is one of the most accessed social media platforms, namely 88 percent of itstotal users in 2019. This video-based media is widely used for several purposes, includingreviewing media literacy that every social media user must understand. This is due to theimpact of social media itself, especially on adolescents who are of a vulnerable age.This study aims to reveal the relationship between the intensity of watchingRemotivi's YouTube channel and the understanding of media literacy among theIndonesian Islamic Student cadres in Yogyakarta Besar. To answer this problem, acombination of Moderate Media Effect theory and Ues and Grativications is used. The typeof research is a survey with data collection using a questionnaire, assisted by interviews,and documentation.Based on the analysis, it was found that there was a relationship between watchingRemotivi's YouTube channel and understanding media literacy in the Yogyakarta BesarIndonesian Islamic Student cadre. This can be seen from the tiered correlation value of 0.47with a significance level of 5%. This shows that there is indeed a relationship betweenwatching the Remotivi channel and literacy understanding even though it is at a moderatelevel.